Crimes in Archival Form: Human Rights, Fact Production, and Myanmar - MacLean, Ken (University of California Press, 2022)
Crimes in Archival Form explores the many ways in which human rights "facts" are produced rather than found. Using Myanmar as his case study, Ken MacLean examines the fact-finding practices of a human rights group, two cross-border humanitarian agencies, an international law clinic, and a global NGO-led campaign. Foregrounding fact-finding, in critical yet constructive ways, prompts long overdue conversations about the possibilities and limits of human rights documentation as a mode of truth-seeking. Such conversations are particularly urgent in an era when the perpetrators of large-scale human rights violations exploit misinformation, weaponize disinformation, and employ outright falsehoods, including deepfakes, to undermine the credibility of those who document abuses and demand accountability in the court of public opinion and in courts of law. MacLean compels practitioners and scholars alike to be more transparent about how human rights "fact" production works, why it is important, and when its use should prompt concern.